Análise da variabilidade espaço-temporal da cobertura do solo e de parâmetros biofísicos na bacia experimental de São João do Cariri - PB. - Silva, Alexandro Medeiros. (2014)
This study aims to analyze the spatiotemporal variations of use and land cover and biophysical parameters in the semiarid of Paraíba State. Moreover, also aims to study the behavior of daily evapotranspiration in different types of uses and land use in the region. The observed data were collected at the meteorological station located at the Experimental Basin of São João do Cariri, located in the semiarid region of Paraíba State. This study compared data observed surface temperature (Ts) at three depths (2, 5 and 10 cm) compared to data estimated by the Surface Energy Balance Algorithm for Land - SEBAL using 12 sensor images Thematic Mapper (TM) satellite LANDSAT 5. These images, two without cloud cover for the dates of 17/12/2004 and 28/10/2009 were used to mapping different types of uses and land use, of biophysical parameters and ET. The results showed that there was a correlation of 0.61 between the estimated and the observed temperatures 5cm deep. The mean values of Ts increased by 2 °C, for net radiation (Rn) the means ranged from 635.3 W/m² and 817.8 W/m², as evapotranspiration showed a decrease in their average value, from 4.39 mm/day to 1.96 mm/day. It is concluded that the methodology used in the determination of Ts, Rn and evapotranspiration in the selected areas, achieved very consistent values, showing a satisfactory methodology. The algorithm SEBAL determined, satisfactorily, the values of Ts, Rn and ET on study area, consistent with observations made in the field.